2010
DOI: 10.1073/pnas.1014716108
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal sequence of cross-regulatory events in root meristem growth

Abstract: A central question in developmental biology is how multicellular organisms coordinate cell division and differentiation to determine organ size. In Arabidopsis roots, this balance is controlled by cytokinin-induced expression of SHORT HYPOCOTYL 2 (SHY2) in the so-called transition zone of the meristem, where SHY2 negatively regulates auxin response factors (ARFs) by protein-protein interaction. The resulting down-regulation of PIN-FORMED (PIN) auxin efflux carriers is considered the key event in promoting diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 34 publications
(58 reference statements)
10
121
1
Order By: Relevance
“…A similar phenotype is observed in loss-of-function mutants of BREVIS RADIX (BRX) (11), another polar localized plasma membrane-associated protein that is also thought to act in the nucleus (11,12). The brx short root phenotype is rescued by second site mutation in BARELY ANY MERISTEM 3 (BAM3), which encodes a receptor-like kinase that is required for suppression of protophloem differentiation on treatment with the peptide ligand, CLAVATA3/EMBRYO SURROUNDING REGION 45 (CLE45) (13).…”
Section: Significancementioning
confidence: 75%
See 2 more Smart Citations
“…A similar phenotype is observed in loss-of-function mutants of BREVIS RADIX (BRX) (11), another polar localized plasma membrane-associated protein that is also thought to act in the nucleus (11,12). The brx short root phenotype is rescued by second site mutation in BARELY ANY MERISTEM 3 (BAM3), which encodes a receptor-like kinase that is required for suppression of protophloem differentiation on treatment with the peptide ligand, CLAVATA3/EMBRYO SURROUNDING REGION 45 (CLE45) (13).…”
Section: Significancementioning
confidence: 75%
“…4 E and F), suggesting it is particularly sensitive to changes in auxin activity. Given that BRX has been implicated in potentiating auxin response (11,24), this would also explain why the penetrance of the observed phenotypes was highest in brx mutants. Remarkably, however, root growth rate and meristem size were only mildly impaired in auxinole-treated roots, despite the absence of the incipient metaphloem cell file (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two plasma membrane-associated proteins OCTOPUS (OPS) and BREVIS RADIX (BRX) are expressed in procambium and protophloem precursors, respectively, and are required for the correct specification of protophloem cells (Scacchi et al, 2010;Truernit et al, 2012). In sieve tube element precursors, the CLAVATA3/EMBRYO SURROUNDING REGION45 (CLE45) peptide inhibits early protophloem development by signaling through the LRR-RLK receptor BARELY ANY MERISTEM3 (BAM3) (Depuydt et al, 2013;Rodriguez-Villalon et al, 2014).…”
Section: Similarities In the Regulation Of Early Vascular Differentiamentioning
confidence: 99%
“…Subsequent analysis showed that BRX mediates the interaction between brassinosteroids and auxin pathways, which is required for root growth (Mouchel et al, 2006). Later analysis suggested that BRX is also involved in cytokinin-mediated inhibition of LR development (Li et al, 2009) and furthermore, the auxin-cytokinin cross talk that coordinates cell division and differentiation in the root tip (Scacchi et al, 2010). Combining high-throughput confocal microscopy imaging, GWAS, and expression analysis, a then-uncharacterized gene encoding an F-box protein was found that underlies the natural variation of root development in a broad set of accessions (Meijón et al, 2014).…”
Section: Using Natural Variation To Identify Regulators Of Root Growtmentioning
confidence: 99%